2018
DOI: 10.3847/1538-3881/aadb8d
|View full text |Cite
|
Sign up to set email alerts
|

KUG 0200-096: Dwarf Antennae Hosting a Tidal Dwarf Galaxy

Abstract: We study a gas rich merging dwarf system KUG 0200-096. Deep optical image reveals an optically faint tail with a length of 20 kpc, giving a visual impression of tidal antenna similar to NGC 4038/39. The interacting dwarf galaxies have B-band absolute magnitudes -18.06 and -16.63 mag. We identify a young stellar clump of stellar mass of 2×10 7 M at the tip of the antenna, possibly a Tidal Dwarf Galaxy (TDG). The putative TDG candidate is quite blue with g − r color index of -0.07 mag, whereas the interacting dw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Pearson et al (2016) further showed that gas-rich dwarf pairs have more extended atomic gas distribution than unpaired analogues. In addition, case studies of several more star-forming dwarf pairs have been carried out recently (Annibali et al 2016;Privon et al 2017;Paudel & Sengupta 2017b;Paudel et al 2018b;Makarova et al 2018;Johnston et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pearson et al (2016) further showed that gas-rich dwarf pairs have more extended atomic gas distribution than unpaired analogues. In addition, case studies of several more star-forming dwarf pairs have been carried out recently (Annibali et al 2016;Privon et al 2017;Paudel & Sengupta 2017b;Paudel et al 2018b;Makarova et al 2018;Johnston et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…sjyoon0691@yonsei.ac.kr (SJY) Massive galaxy mergers have been studied in great detail in both observation and numerical simulations (Barnes 1992;Naab & Ostriker 2009;Duc et al 2011). The dwarf-dwarf interactions, on the other hand, are only starting to be explored as a population (Stierwalt et al 2015;Pearson et al 2016;Besla et al 2018;Paudel et al 2018a). This is partly because such systems are possibly not common in the local universe or they are fainter, which makes them harder to detect.…”
Section: Introductionmentioning
confidence: 99%
“…While dwarf-dwarf mergers were expected to be more common in early universe (Klimentowski et al 2010;Fitts et al 2018), recent observations have shown that they are also present in current epoch. The interaction between dwarf galaxies in isolated environments are frequently reported, however they are rare around massive host (Stierwalt et al 2015;Paudel et al 2018a;Kado-Fong et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Kado-Fong et al (2020) found that 15%-20% of nearby dwarf galaxies with extreme starburst activities show signs of tidal debris. In addition to the above relatively systematic studies, a few more case studies of gas-rich dwarf pairs have also been carried out (Annibali et al 2016;Privon et al 2017;Paudel & Sengupta 2017b;Paudel et al 2018b;Makarova et al 2018;Johnston et al 2019).…”
Section: Introductionmentioning
confidence: 99%